2015
DOI: 10.1016/j.biopsycho.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

High cardiac vagal control is related to better subjective and objective sleep quality

Abstract: HighlightsCardiac vagal control (CVC) was measured during an extended standardized baseline.Subjective and polysomnographic variables of sleep quality were assessed.Higher CVC was found to be associated with better subjective and objective sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 63 publications
(103 reference statements)
7
72
1
1
Order By: Relevance
“…Others have shown that the impact of stress on the ANS during sleep is evident in real-life situations: higher levels of daily worry and stressors were associated with faster HR and lower HRV during waking and the subsequent sleep period in healthy men and women, with worry duration mediating the effect (Brosschot et al, 2007). On the other hand, higher resting vagal activity before bed is associated with better subjective and objective sleep quality in young women (Werner et al, 2015). …”
Section: 4 Discussionmentioning
confidence: 99%
“…Others have shown that the impact of stress on the ANS during sleep is evident in real-life situations: higher levels of daily worry and stressors were associated with faster HR and lower HRV during waking and the subsequent sleep period in healthy men and women, with worry duration mediating the effect (Brosschot et al, 2007). On the other hand, higher resting vagal activity before bed is associated with better subjective and objective sleep quality in young women (Werner et al, 2015). …”
Section: 4 Discussionmentioning
confidence: 99%
“…The investigation took place as part of a larger study in the Clinical Stress and Emotion Lab of the University of Salzburg (for further details see Werner, Ford, et al, 2015; Werner, Schabus, Blechert, Kolodyazhniy, & Wilhelm, 2015) including four visits to the lab (entrance examination and three nights in the lab). The whole study spanned 11 days.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Results concerning pre-to postsleep changes in emotional reactivity to the aversive film in relation to REM sleep, and regarding links between resting CVC (wake as well as sleep stage related) and sleep quality (subjective as well as objective variables) have been reported separately (Werner, Ford, et al, 2015; Werner, Schabus, et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Subjective sleep quality parameters, including the time it takes to fall asleep at night, have been associated with reduced parasympathetic tone during wake in clinical populations (Hovland et al, 2013;Yang et al, 2011), and in healthy young women without sleep disorders (Werner et al, 2015). During waking hours, adequate parasympathetic control of the heart may serve to accelerate inhibitory, de-arousal processes necessary for falling asleep at night, while reduced parasympathetic tone may impair these processes (Werner et al, 2015). Whether reduced parasympathetic tone throughout the day results from, or contributes to more difficulty falling asleep at night is not clear and warrants further research.…”
Section: Discussionmentioning
confidence: 99%